DOES POLITICAL CONNECTION, SALES GROWTH, AND INSTITUTIONAL OWNERSHIP AFFECT ON TAX AVOIDANCE? - Dita Tristianti Sagita Putri; Aristantia, Selvia Eka (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine the effect of political relations, sales growth, and institutional ownership on tax avoidance partially and simultaneously. The method used in this study is a quantitative method. The population in this study were 55 manufacturing companies in the consumer goods industry sector listed on the IDX during the 2017-2019 period. The sample of this research is 99 companies with purposive sampling technique. The data analysis technique of this study uses multiple linear regression analysis with the help of SPSS 25 software. The results of this study indicate that partially the political variable connection and sales growth have no significant effect on tax avoidance, but the institutional ownership variable has a significant effect on tax avoidance. Meanwhile, simultaneously, the variables of political connection, sales growth and institutional ownership has a significant effect on tax avoidance.